Effects of Steroidal and Non Steroidal Drugs on the Neovascularization Response Induced by Tumoral TA3 Supernatant on CAM from Chick Embryo - JORGE ZÚÑIGA; MARCELA FUENZALIDA; ANÍBAL GUERRERO; JULIO ILLANES; ALFREDO DABANCENS; EUGENIA DÍAZ; DAVID LEMUS (Biological Research, 2003)
Angiogenesis, the development of new blood vessels from the existing vascular network, may result as a consequence of the increase or decrease of proangiogenic or antiangiogenic factors, respectively. The tumor itself could up-regulate the production of angiogenic factors. Recently, we established that the steroidal drug betamethasone in low concentration inhibit the neovascularization promoted by TA3 Ts on CAM of chick embryos. We describe here the effects of the non-steroidal drug ketoprofen, alone or in association with betamethasone, on the angiogenesis promoted by TA3 Ts on CAM. The main finding reported here is that the formation of new blood vessels is strongly inhibited by low concentrations of ketoprofen. The association of both drugs produced a synergistic effect, significantly decreasing tumoral supernatant angiogenesis. It is known that steroidal anti-inflammatory drugs inhibit the enzymes required for the production of prostaglandins through a nuclear GR mediated mechanism. This may operate as a general mechanism in endothelial cells as well. Considering that the induction of COX 1 and COX2 are inhibited by ketoprofen, and that these enzymes are located in the stromal compartment of the CAM, we propose that its antiangiogenic effect may occur via inhibition of the two COX isoforms. In fact, we found that ketoprofen induced apoptosis in both the stromal fibroblast and endotelial cells. The potentiated effect of the combination of betamethasone and ketoprofen may have some therapeutic projections in the control of pathological angiogenesis